Similarities between the target and the intruder in naturally-occurring repeated person naming errors - Serge eBredart; Benoit eDardenne (Frontiers in Psychology, 2015)
The present study investigated an intriguing phenomenon that did not receive much attention so far: repeatedly calling a familiar person with someone else’s name. From participants’ responses to a questionnaire, these repeated naming errors were characterized with respect to a number of properties (e.g., type of names being substituted, error frequency, error longevity) and different features of similarity (e.g., age, gender, type of relationship with the participant, face resemblance and similarity of the contexts of encounter) between the bearer of the target name and the bearer of the wrong name. Moreover, it was evaluated whether the phonological similarity between names, the participants’ age, the difference of age between the two persons whose names were substituted, and face resemblance between the two persons predicted the frequency of error. Regression analyses indicated that phonological similarity between the target name and the wrong name predicted the frequency of repeated person naming errors. The age of the participant was also a significant predictor of error frequency: the older the participant the higher the frequency of errors. Consistent with previous research stressing the importance of the age of acquisition of words on lexical access in speech production, results indicated that bearer of the wrong name was on average known for longer than the bearer of the target name.